The use of text-mining software to facilitate screening of literature on centredness in health care - Emma Forsgren; Sara Wallström; Caroline Feldthusen; Niklas Zechner; Richard Sawatzky; Joakim Öhlén (Systematic Reviews, 2023)
Abstract Research evidence supporting the implementation of centredness in health care is not easily accessible due to the sheer amount of literature available and the diversity in terminology and conceptualisations used. The use of text-mining functions to semi-automate the process of screening and collating citations for a review is a way of tackling the vast amount of research citations available today. There are several programmes that use text-mining functions to facilitate screening and data extraction for systematic reviews. However, the suitability of these programmes for reviews on broad topics of research, as well as the general uptake by researchers, is unclear. This commentary has a dual aim, which consists in outlining the challenges of screening literature in fields characterised by vague and overlapping conceptualisations, and to exemplify this by exploratory use of text-mining in the context of a scoping review on centredness in health care.